Shari'ah and regulatory issues of Islamic trade finance in Malaysia - Sharifah Faigah Syed Alwi (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2012)
One of the main facilities offered by Islamic banks in Malaysia is trade finance. Operational practices of Islamic trade finance (ITF) in Islamic banks differ from one another. These practices raised some questions or issues among bankers, Shari'ah advisors and experts in ITF. Thus, this research aims to highlight the Sharf'ah issues on the operation of ITF facilities in Islamic banks. The ITF facilities must conform to the laws and regulations imposed by Bank Negara Malaysia (BNM) and are bound to follow rules and standards of the International Chamber of Commerce (ICC) for trade finance transactions. Therefore, this research also investigates the Sharf'ah issues in relation to these governing rules and regulations. This research adopts the qualitative method as the main research methodology. Shari'ah issues on the operation and governing rules of ITF are gained from semi-structured interviews conducted with bankers who directly involved with the operation of ITF, Shari'ah officers, Shari'ah advisors and experts of ITF and international trade in Malaysia. From the interviews, this research discovers many Shari'ah issues related to ITF facilities and the ICC rules such as the issue of converting the contract of letter of credit (LC) wakalah to LC murababahah, the issue of charging fees for bank guarantee which is using kafalah contract and the issue of the element of interest in the ICC rules. This research analyzes those issues by determining whether they are in line with Shari'ah principles. Generally, many of ITF facilities are Sharf'ah compliant except for a few facilities which need to be amended. Hence, some possible solutions to resolve the Shari'ah issues are proposed to BNM, Islamic banks and other related authorities.